"Data Warehousing, Data Mining, and OLAP" - Berson (Alex); Smith (Stephen J) (2006)
Data Warehousing Mining
42215a.jpg;42215b.jpg;42215c.jpg;42215d.jpg;42215e.jpg;42215f.jpg;42215g.jpg;42215h.jpg;42215i.jpg;42215j.jpg;42215k.jpg
22.5
Keywords: Data Warehousing Mining